Lycopene ameliorates diabetes-induced pancreatic, hepatic, and renal damage by modulating the JAK/STAT/SOCS signaling pathway in rats - Ozlem Ozmen; Melda Şahin; Senay Topsakal; Şerife Taşan; Uğur Şahi̇n (Iranian Journal of Basic Medical Sciences)
Objective(s): Emerging evidence suggests that the JAK/STAT/SOCS signaling pathway is crucial for maintaining homeostasis, and its dysregulation contributes to diabetes development. This study aimed to evaluate the roles of SOCS-1 and SOCS-3 in the pancreas, liver, and kidney and to explore the involvement of the JAK/STAT pathway in the molecular mechanisms underlying their effects on inflammation and apoptosis, as well as organ injury in a diabetes mellitus (DM) model. Additionally, we sought to elucidate the role of the JAK/STAT/SOCS pathway in mediating the effects of lycopene (LYC).Materials and Methods: Forty Sprague-Dawley rats were divided into control, DM, LYC, and LYC+DM groups. Diabetes was induced in the DM groups using streptozotocin. LYC was administered to the LYC and LYC+DM groups for 30 days. After the study, pancreas, liver, and kidney tissues were analyzed using histopathological, immunohistochemical, and PCR methods.Results: Significant vacuolization and degenerative changes were observed in the DM group’s pancreatic islet cells. Kidney and liver tissues showed hyperemia, hemorrhage, and degenerative changes. Immunohistochemical analysis revealed increased expression of Cas-3, TNF-α, IFN-α, and IL-6, while IL-10 was significantly reduced in the DM group. PCR analysis showed elevated levels of TNF-α and Cas-3, with decreased SOCS-1 and SOCS-3 expression in the DM group.Conclusion: This study highlights the therapeutic potential of targeting the JAK/STAT/SOCS pathway with lycopene, demonstrating its promise in mitigating diabetes and related complications.